Pengaruh Rasio Etanol-Air terhadap Rendemen dan Aktivitas Sitotoksik Ekstrak Daun Azadirachta Indica - Sinaga, Samuel Billie Tua; Ramanda, Putri; Mawakhid, Oki Rokhim; Shari, Winda; Wiradimafan, Khafit; ., Avidlyandi; Adfa, Morina (LPPM Universitas Dharma Andalas, 2026)
Neem leaves (Azadirachta indica) are widely recognized as a rich source of diverse bioactive compounds that exhibit promising pharmacological activities, including anticancer potential. Nevertheless, studies investigating how variations in solvent composition influence extract yield and cytotoxic activity remain limited. Therefore, this research aimed to evaluate the effect of different ethanol–water solvent ratios (50%, 70%, and absolute ethanol) on both the extraction yield of neem leaves and their cytotoxic activity against Artemia salina Leach. The extraction procedure combined sonication and subsequent maceration using the three solvent systems to enhance compound recovery. Cytotoxic assessment was performed through the Brine Shrimp Lethality Test (BSLT) at concentrations of 1000, 500, 100, and 10 ppm, utilizing 48-hour-old larvae with three experimental replicates. Larval mortality was observed after 24 hours of exposure, and LC₅₀ values were determined using probit analysis and linear regression methods. The results demonstrated that extraction with 50% ethanol produced the highest yield (23.5%), followed by 70% ethanol (20.8%) and absolute ethanol (16.10%). In contrast, the strongest cytotoxic activity was observed in the 70% ethanol extract, which exhibited the lowest LC₅₀ value (62.87 ppm), followed by the 50% ethanol extract (64.23 ppm) and the absolute ethanol extract (99.15 ppm). These findings indicate that solvent ratio significantly influences both extraction efficiency and cytotoxic potency; however, extract yield was not directly correlated with cytotoxic activity. Importantly, all extracts demonstrated LC₅₀ values below 100 ppm, suggesting notable toxicity and highlighting their potential as candidates for developing anticancer raw materials.